Cooling Systems for High-Speed Machines—Review and Design Considerations - Matthew Meier; Elias G. Strangas (Energies)
High-speed machines are attractive to many industries due to their small size and light weight, but present unique cooling challenges due to their increased loss and reduced surface area. Cooling system advancements are central to the development of faster, smaller machines, and as such, are constantly evolving. This paper presents a review of classical and state-of-the-art cooling systems. Each cooling method—air cooling, indirect liquid cooling, and direct liquid cooling—has potential use in cooling high-speed machines, but each comes with unique considerations, which are discussed. An example design process highlights the interdependence of the electromagnetic and thermal design choices, illustrating the necessity of integrating the electromagnetic and thermal designs in a holistic approach.